Me valoro como soy - Becerra Malca, Rocío del Pilar (2020)
The present work called "God Created Me, I Am the only one" focuses on the Social Personal area of children of 03-year-olds, whose learning session design, theoretical and pedagogical support are based on the literature collected about the session and area, also in the information provided by the Ministry of Education and in the pedagogical technical experience of the responsible person. In the learning activity the competence is: Build your identity, capacity: values himself and performance:recognizes their needs, feelings, interests and preferences; differences from those of others, through words, actions, gestures or movements. The purpose of this activity is for students to recognize their main characteristics, considering the differences between them through words, gestures or movements _x000D_ We must understand the importance of building the child's identity in their integral training in school, which will allow them to train as a person and citizen.